Rebel as/in Creative Annihilator: Resistance in Nazrul Islam and Bairagi Kainla - Phuyal, Komal Prasad (Nepal Journal of Multidisciplinary Research, 2024)
Background: Bangladeshi poet Kazi Nazrul Islam (1899-1976) and modern Nepali poet Bairagi Kainla (1939-) invent their unique position to envision the contour of the rebel in “The Rebel” (1922) and “Drunk Man’s Speech to the Street after Midnight” (1960) respectively: their rebels voice for complete annihilation of the old order in search of the new one. Methods: Using Marxist dialectics as implied in later Foucault and David Jeffer’s concept of resistance, this study examines the modes of resistance that enable creative writers to uphold the contour of the rebellious self-seeking of the space of creative anarchy. Results: The rebellious self recognizes the space akin to the primordial universe which both the poets assert sets the ground for an entirely new order. As nonconformist poets, Islam and Kainla delve into the structure until they uncover the last remnant of the oppressive order to expose the inequalities such structures promote in each society. Conclusion: The mode of resistance that the poetic persona adopts to view the existing social order presents a novel way of responding to the tyranny of their contemporary time. Islam’s rebel takes up the form of anarchist, debunking the firm structure of the British Raj. On the other hand, Kainla’s persona poetically gets intoxicated to issue an order to the intellectuals to walk out on the street in search of change. Kainla knows that the society is well-prepared to ward off the ghost of the existing tyranny of King Mahendra. In both cases, the revolting self emerges larger than the political order. Novelty: Approaching the poetic texts from the perspective of resistance helps understand the attempts and vision of creative genius to fight against the oppressive power structure of their times.